Color Perception in Protanomalous Female Macaca fascicularis. (April 2019) - Widayati, Kanthi A.; Saito, Atsuko; Suryobroto, Bambang; Mikami, Akichika; Koida, Kowa
Protanomalous females with X chromosome-linked color vision deficiency exhibit mild abnormalities, whereas dichromats show a distinct deficiency in discriminating certain color pairs. Dichromats have an advantage in detecting a textured target when it is camouflaged by red-green colors, owing to their insensitivity to these colors. However, it is not certain whether protanomalous females possess a similar advantage in breaking camouflage. Here, we introduce an animal model of dichromatic macaque monkeys and protanomalous females. We examined whether protanomalous females have the same advantage in breaking color camouflage as shown by dichromatic macaques. We also tested whether they could discriminate a certain color pair that trichromats could, where the dichromats are confused. Our experiments show that protanomalous macaques can break color camouflage, similar to dichromats, and can discriminate colors similarly to trichromats. Protanomalous females are thus thought to have the combined ecological advantages of being both trichromats and dichromats.